Privatisation and commercialisation in Nigeria: Implications and prospects for good governance - T. O. Asaolu; O. Oyesanmi; P. O. Oladele; A. M. Oladoyin (South African Journal of Business Management, 2005)
The privatisation and commercialisation Decree No. 25 of 1988 (amended 1999) which provided the legal backing for the Technical Committee of Privatisation and Commercialisation (TCPC), began the major paradigm shift in the conceptualisation of public enterprises in Nigeria. The paper primarily examined the privatisation exercise in Nigeria since 1988. It also attempted to provide measures that will simplify the complex process of privatisation with the hope of lessening the probability of crisis. The paper considered the impact of privatisation on performance of privatised companies, changes in employment and the increase in the prices of commodities of the enterprises vis-à-vis their gross income towards the overall good governance of the Nigerian society.The data for the paper were mainly secondary; and were drawn from the financial statements of companies in the stock Exchange and other stock Exchange reports, Central Bank Bulletins, publications and published reports of the Bureau of Public Enterprises. Newspapers and publication of the Federal Office of Statistics are other sources. The data were analysed by trend analysis using absolute figures, percentages and ratios based on the past record on privatisation in Nigeria.However, the study discovered that only a few successful enterprises, Flour Mills, African Petroleum, National oil and Chemical Marketing Company Limited (NOLCHEM) were partially privatised. The commercialisation of enterprises such as National Electric Power Authority (NEPA), Nigeria Telecommunications (NITEL) and Nigerian National Petroleum Corporation (NNPC), hardly showed any significant improvement in their operational and economic performance.The papers showed that employment levels were affected by privatisation. Between 1989 and 1993, the public sector accounted for more job losses than privatised companies. When privatised firms employment rose, public and private sectors still had lower employment levels. The sharp increase in prices between 1992 and 1994 did not create a sufficient increase in gross earnings for 1994. The results revealed that a reduction in public control would have an effect (at least in the short term) on prices. Profits increase but the extent to which this increase can attributed to reduction of government controls is not clear. Three banks witnessed sharp increase in investments and profitability immediately after privatisation, and there was a slight decrease before another increase. Results showed that privatisation has improved company performance, especially in the efficiency of resources utilisation. Higher profit to capital employed ratios has been witnessed since privatisation. Debt/Total Asset ratios have not been affected in any adverse way. Results from the study also revealed that price increases in excess of 200% occurred immediately after privatisation. This perhaps has an effect on the profits of the companies (especially those that still maintained monopoly status for a while.However, one fact is clear: the heydays of public enterprises in Nigeria are gone for good. It was on this note that the study concluded that privatisation is the appropriate economic recipe to achieve the much desired human development and good governance.
Keywords: 650